PEREKONOMIAN DESA KOTA BARU KECAMATAN GERAGAI KABUPATEN TANJUNG JABUNG TIMUR 1984-2009 - Dwi Kusuma, Siti Heidi Karmela (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract The main problem of this research is "New Urban Village Economy in Growth,  Development and the Impact on Economic Life of the society Period 1984-2009". The purpose of this research is to describe the driving and supporting factors as well as the process of growth and development of the economy of the Kota Baru, as well as explain the impact to the economic life of the society and the progress of the Kota Baru. The research used  history method, through several stages of heuristics, criticism, interpretation and historiography.The findings in the field show that Kota Baru has experienced growth and economic development in the long term from 1984-2009. So many supporting factors and driving factors that cause the process of growth and development is included with the modernization of the economy. Even as evidence of the success of growth and economic development, Kota Baru has become an independent integrated village pilot center by the central government and the East Tanjung Jabung Regency Government which will have a positive impact on the local economy as well as the economic life of the people of Kota Baru Village. Keywords: Kota Baru Village, Growth, Development, Village Economy, Modernization, Independent Integrated village.